The Correlation Level Of Thyroid Stimulating Hormone Andthyroxinewith Spontaneus Abortion - Yellyta Ulsafitri; Rahmatina Rahmatina (Journal of Midwifery, 2018)
Abortion is one of the causes of maternal death. The World Health Organization (WHO) estimates that 15-20% of maternal deaths are caused by abortion. Abnormal level of TSH and T4 during pregnancy will be at risk of abortion because the T4 hormone acts to regulate the body's metabolic processes. The purpose of this study to determine the relationship of TSH and T4 levels in the incidence of abortion.         The research design is observational with cross sectional approach which is implemented in regency general hospital of Dr. Rasidin, hospital of Dr. Reksodiwiryo,Bhayangkara hospital, Islam hospital of IbnuSina Padang, and Biomedical Laboratory Faculty of Medicine Andalas University in Padang from September to November 2017. The study population is all pregnant women with gestational age ≤ 20 weeks with diagnosis of abortion. The sample of research 58 respondents by using consecutive sampling technique Examination of TSH and T4 using ELISA method. Test the normality of data by Kolmogorov Smirnov test. Analysis of comparative data by using Pearson correlation test.         The conclusion of this study are the mean serum TSH level is 2.39 ± 1.59 mIU / I and the mean serum T4 level was 8.02 ± 1.43 μg / dl. There is no statistically significant relationship between TSH and T4 levels in aborted event, with p = 0.07 (p> 0,05), with r = -0,23, the relation test is weak, the direction was negative which means more high levels of TSH, the smaller  T4 levels in  mother abortion        The conclusion, the study proves that, there is no significant correlation between TSH and T4 levels in the incidence of abortion.